Exploring the Association Between Overstay Fixation During an Electronic Trail Making Test and Cognitive Functional Independence After Stroke. - Akiyama, Ryoto; Kondo, Ken; Noguchi, Naoto; Kim, Siyeong; Lee, Bumsuk (NeuroRehabilitation, 2026)
Background/Aims: The aim of the present study was to examine the potential association between a specific gaze behavior, "overstay fixations," observed during the Trail Making Test, and cognitive functional independence after stroke. Methods: This study was a cross-sectional, observational study. Hospitalized patients with mild stroke (n = 12) and healthy young adults (n = 19) performed the electronic version of Trail Making Test. The number of overstay fixations and the total completion time were measured. In the patients with mild stroke, the total time in conventional Japanese version of Trail Making Test and the cognitive scores in Functional Independence Measure were measured. Findings: The mild stroke group showed significantly more overstay fixations as task difficulty increased (p = 0.005). A significant correlation existed between the overstay fixations during the electronic version of Trail Making Test part A and the cognitive Functional Independence Measure scores for Comprehension (r = -0.643) and Memory (r = -0.610). Multiple regression revealed that the total time and overstay fixations in the electronic version of the Trail Making Test were more strongly associated with the Comprehension score (R² = 0.850) compared with the total time in the paper-based Trail Making Test (R² = 0.397). Similarly, the Memory score showed stronger associations with the total time and overstay fixations in the electronic version of the Trail Making Test (R² = 0.684) than with the total time in the paper-based version (R² = 0.391). Conclusions: The overstay fixation was associated with specific domains of cognitive functional independence in patients with mild stroke.